Belief in a just world as a moderator in the face of ageism: a comparative analysis of just world theory and worldview verification theory - Kim, Eunha (Frontiers in Psychology, 2024)
Based on the Just World Theory (JWT) and Worldview Verification Theory (WVT), we conducted two studies to investigate whether a belief in a just world for the self (BJW-self) moderates the relationship between perceived discrimination against older adults (ageism) and selfesteem in a sample of South Koreans older adults.In Study 1, we collected survey data from 304 South Koreans aged 65 and older using the scales of perceived ageism, BJW-self, and self-esteem. In Study 2, we randomly assigned 140 South Koreans aged 65 and older to read one of two articles: one describing ageism as pervasive or one describing ageism as rare. Results: Study 1 revealed that perceived ageism negatively correlated with self-esteem at low levels of BJW-self than at high levels of BJW-self. In Study 2, older adults who were told that ageism is pervasive had lower self-esteem than those who were told that ageism is rare, but this difference was greater for those who rejected BJW-self than for those who endorsed BJW-self. Discussions: The results support the notion of the JWT that BJW-self mitigates the deleterious effects of perceived ageism on self-esteem.